Interaction of N with White-solidified Cast Iron Model Alloys: The Effect of Mn and Cu on the Formation of Fe and Si Nitrides - Kante, Stefan; Leineweber, Andreas (Journal of Casting & Materials Engineering, 2021)
Surface remelting and subsequent nitriding improves the surface properties of cast irons. Upon remelting, a white-solidified surface layer forms, which contains coarse Si-free eutectic cementite (θ) and Si-enriched ferrite, pearlite or martensite in the intercarbidic regions between the eutectic θ. Nitriding produces a compound layer at the surface, which is composed of ε and γ’-iron (carbo)nitrides and enhances the corrosion resistance. Nitriding of white-solidified Fe-C-Si alloys, being model materials for remelted low-alloy ferritic cast irons, has shown that Si dissolved in α-Fe notably affects the formation of ε and γ’ in intercarbidic regions while Si simultaneously precipitates as amorphous nitride, X. Under process conditions only allowing for the formation of γ’ in pure Fe, Si dissolved in α-Fe promotes the formation of ε over the formation γ’, whereas Si-free eutectic θ transforms into nitride following the sequence θ → ε → γ’. The present work studies the nitriding of white-solidified Fe-3.5wt.%C-3wt.%-M alloys with additions of M = 1 wt.% Mn, 1 wt.% Cu or 1 wt.% Mn + 1 wt.% Cu, serving as model materials for remelted pearlitic cast irons. The presence of Mn and/or Cu causes notable deviations from the nitriding behavior known from Fe-C-Si alloys. Mn accelerates the precipitation of X in intercarbidic regions and obstructs the transformation of ε formed from Si-free θ into γ’. Cu promotes the formation of γ’ in Si-rich intercarbidic regions, surpassing the ε-promoting effect of Si.